2000
DOI: 10.4049/jimmunol.164.4.2046
|View full text |Cite
|
Sign up to set email alerts
|

Stat6 Signaling Promotes Protective Immunity Against Trichinella spiralis Through a Mast Cell- and T Cell-Dependent Mechanism

Abstract: Studies in mice infected with the gastrointestinal nematode parasite Nippostrongylus brasiliensis demonstrated that IL-4/IL-13 activation of Stat6 suppresses development of intestinal mastocytosis and does not contribute to IL-4/IL-13 production, but is still essential for parasite expulsion. Because expulsion of another gastrointestinal nematode, Trichinella spiralis, unlike N. brasiliensis expulsion, is mast cell dependent, these observations suggested that T. spiralis expulsion would be Stat6 independent. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
174
1
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(183 citation statements)
references
References 46 publications
6
174
1
2
Order By: Relevance
“…We have shown that IL-13 (and IL-4R␣), but not IL-4, is required for T. spiralis expulsion. Urban et al (20) found that worm expulsion was enhanced when mice were treated with exogenous IL-4, but, like us, found that mice deficient for IL-4 expel their worm burden at the same rate as wild-type mice. They also showed that IL-4-deficient mice failed to expel if treated with sIL-13R␣2, thus indicating that both IL-13 and IL-4 are important in resistance to this nematode.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…We have shown that IL-13 (and IL-4R␣), but not IL-4, is required for T. spiralis expulsion. Urban et al (20) found that worm expulsion was enhanced when mice were treated with exogenous IL-4, but, like us, found that mice deficient for IL-4 expel their worm burden at the same rate as wild-type mice. They also showed that IL-4-deficient mice failed to expel if treated with sIL-13R␣2, thus indicating that both IL-13 and IL-4 are important in resistance to this nematode.…”
Section: Discussionmentioning
confidence: 55%
“…These different findings may be attributable, at least in part, to the different mouse strains used in these studies. STAT-6 is required for both IL-4 and IL-13 signaling, and is essential for the expulsion of both T. spiralis and N. brasiliensis from the intestine (20,21). We have shown that IL-13 (and IL-4R␣), but not IL-4, is required for T. spiralis expulsion.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…I sc responses to PGE 2 and histamine were significantly enhanced only in the IL-4C-treated ϩ/ϩ mice, suggesting that these prosecretory effects of IL-4 are mast cell dependent. Because IL-4 induction of intestinal mastocytosis and mast cell degranulation are STAT6 independent (22,23) (Fig. 3), we expected that the mast cell-dependent mechanism by which IL-4 increases the response to histamine and PGE 2 would also be STAT6 independent.…”
Section: Cytokine Mast Cell and Stat6 Dependence Of Pge 2 And Hismentioning
confidence: 99%
“…Studies using IL-4 or IL-4-receptor-α deficient mice revealed that IL-4 has a crucial role in worm expulsion [43,44]. However, it is not clear whether IL-5 and/or eosinophils can be implicated in the protective response of the host against the parasite.…”
Section: Protection By Eosinophils In Murine Modelsmentioning
confidence: 99%